Development of Consumption and Supplying Energy in Indonesia’s Economy - Faizah, Siti Inayatul; Husaeni, Uus Ahmad (International Journal of Energy Economics and Policy, 2018)
One of the problems faced by Indonesia is the increasing energy consumption and tend to be wasteful, while the fossil energy reserves are depleted and the development of alternative energy is slow, so it is feared Indonesia experiencing energy crisis. The purpose of this article is to analyze the development of consumption and energy supply in Indonesia from 2007-2017. Data analysis in this research is by using combination between trend analysis and descriptive analysis. So the conclusion of this article shows that energy consumption in all sectors, namely industrial sector, household sector, transportation sector, commercial sector and other sectors tend to increase from year to year. Meanwhile, overall energy supply tends to increase, but with a smaller increase than the increase in consumption. And to overcome energy problem in Indonesia is needed energy conservation that is by conducting energy saving campaign, determination of energy conservation law, and establishment of energy conservation center. Furthermore, the Indonesian government should have a long-term plan to divert the use of energy from non-renewable sources to renewable energy use, such as the use of water, wind, biomass, biodiesel, biogas and other sustainable energy sources. Keywords: energy conservation, energy consumption, energy supply, Indonesian economy. JEL Classifications: D11, Q1, Q4 DOI: https://doi.org/10.32479/ijeep.6926